Morphometric characterization and zoometric indices of female Bali cattle reared in Lombok Tengah District, West Nusa Tenggara, Indonesia - Adi Tiya Warman; Galih Trie Fadhilah; ‪Alek Ibrahim‬; ‪Bayu Andri Atmoko‬; Endang Baliarti; Panjono Panjono (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Warman AT, Fadhilah GT, Ibrahim A, Atmoko BA, Baliarti E, Panjono. 2023. Morphometric characterization and zoometric indices of female Bali cattle reared in Lombok Tengah District, West Nusa Tenggara, Indonesia. Biodiversitas 24: 966-974. Livestock body conformation can be described by using their morphometric characteristics and zoometric indices. This study aims to provide information about female Bali cattle's (Bos javanicus) morphometric characterization and zoometric indices using principal component analysis (PCA). The study was conducted by using 149 heads of the female Bali cattle reared by smallholder farmers in Lombok Tengah District, West Nusa Tenggara Province, Indonesia. Morphometric characteristics in this study consists of body length (BL), withers height (WH), chest girth (CG), chest width (CW), chest depth (CD), rump height (RH), rump width (RW), head length (HW), and head width (HW). Therefore, the zoometric indices in this study consist of body index (BI), body ratio (BR), cephalic index (CeI), compact index (CoI), conformation index (CnI), depth index (DI), index of compression (IC), height index (HI), height slope (HS), length index (LI), over increase index (OII), thoracic development (TD), transverse pelvic (TP), and weight (W). Data were analyzed by descriptive analysis and factor analysis (principal component analysis/PCA) using SPSS 25.0 program. The average body measurements for BL, WH, CG, CW, CD, RH, RW, HL, and HW were 108.40, 108.35, 148.54, 34.54, 57.50, 106.28, 32.03, 34.66, and 19.10 cm, respectively. The highest correlation coefficient (r) in morphometric characteristics was shown between RH and WH (0.744) and in zoometric indices between BR and HS (0.997). The PCA for morphometric characteristics revealed two factors of PC1 (BL, CG, CW, CD, RW, and HL) and PC2 (WH, RH, and HW), which explain about 67.50% of the total variation. The PCA for zoometric indices revealed four factors of PC1 (CoI, CnI, DI, LI, TD, TP, W), PC2 (BR, HS, and OII), PC3 (BI, IC), and PC4 (CeI), which explain about 90.64% of the total variation. It was concluded that six morphometric characteristics (BL, CG, CW, CD, RW, and HL) were important to describe the body conformation of female Bali cattle and could be used as selection criteria.